2010
DOI: 10.1128/jvi.02289-09
|View full text |Cite
|
Sign up to set email alerts
|

Killing of Avian and Swine Influenza Virus by Natural Killer Cells

Abstract: Today, global attention is focused on two influenza virus strains: the current pandemic strain, swine origin influenza virus (H1N1-2009), and the highly pathogenic avian influenza virus, H5N1. At present, the infection caused by the H1N1-2009 is moderate, with mortality rates of less <1%. In contrast, infection with the H5N1 virus resulted in high mortality rates, and ca. 60% of the infected patients succumb to the infection. Thus, one of the world greatest concerns is that the H5N1 virus will evolve to allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 40 publications
(62 reference statements)
1
66
0
Order By: Relevance
“…Indeed, whereas the influenza HA is a lectin, and its interaction with NKp46/NCR1 causes direct killing of the infected cells (8,17), other ligands, such as the ligand found on MCA-induced sarcoma, cause indirect killing by cytokine secretion (14). Notably, the ligand on MCA-transformed cells undergoes immune editing by NKp46/NCR1 pressure (14), whereas the ligand on D122 cells described in this study apparently does not.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Indeed, whereas the influenza HA is a lectin, and its interaction with NKp46/NCR1 causes direct killing of the infected cells (8,17), other ligands, such as the ligand found on MCA-induced sarcoma, cause indirect killing by cytokine secretion (14). Notably, the ligand on MCA-transformed cells undergoes immune editing by NKp46/NCR1 pressure (14), whereas the ligand on D122 cells described in this study apparently does not.…”
Section: Discussionmentioning
confidence: 74%
“…In this study, we show that NKp46/NCR1 recognizes an unknown ligand(s) expressed by the metastatic cell lines B16 and D122, as well as by D122 tumors and metastases. We demonstrate that unlike the HA protein that interacts with the sialic residues of the NKp46/NCR1 (7,8,17), the unknown D122 ligand(s) of NKp46/NCR1 binds this receptor in a sialic acidindependent manner. We further demonstrate that the tumor ligand(s) expressed by PD1.6 and D122 cells contains a protein component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we found that intrahepatic frequency of NKp46 High NK cells inversely correlated with HCV loads. Whether NKp46 recognizes a HCV-derived protein [17][18][19][20][21] or interacts with a yet unknown NKp46 ligand, as has been suggested for malignant transformed cells, 40,41 remains to be clarified. However, blocking of NKp46 significantly reduced the capability of both circulating and intrahepatic NK cells to block HCV replication, suggesting a role of NKp46 in the regulation of anti-HCV immune responses.…”
Section: Nk Cells (Supportingmentioning
confidence: 99%
“…Moreover, NKp46 plays an important role in the killing of virus-infected cells by interacting with viral proteins. [17][18][19][20][21] Studies on NKp46 in HCV infection are controversial, because both reduced and increased surface expression have been reported. 5,[7][8][9] In this context, it is of interest that earlier studies showed that the surface expression of NKp46 may vary in different human peripheral blood NK cells, and that the NKp46 phenotype of NK clones correlates with cytolytic activity.…”
mentioning
confidence: 99%